Development of Warm Mix Asphalt with the Aid of Microstructural Characterization - Al Mamun, Abdullah; Sirin, Okan; Masad, Eyad (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The polymer-modified asphalt (PMA) reveals different types of advantageous properties depending on the type of polymer. However, one of the unwanted changes in PMA is the required higher temperature for mixing and compaction. To reduce these temperatures, different percentages of warm mix additive (WMA) have been utilized. However, the addition of WMA can lead to different micro-nano structural changes in the PMA and can subsequently affect overall performance of the asphalt pavement. Therefore, understanding the microstructural behavior of the polymer and additive modified asphalt is crucial to achieve the desired performance. This study attempts to substantiate the effect of WMA in three different PMAs and subsequent changes in different properties. These changes can be scrutinized from different perspectives; however, correlating a basic microstructural property to the rheology of asphalt is an effective way to understand the mechanism and predict performance. In this regard, the need for microstructural evaluation in terms of nano-adhesive properties is recommended. It is expected that assessing the adhesive properties by simulating the field condition can address the phase integrity and crystal structure of PMA and subsequent desired performance of the asphalt pavement. Finally, the observed adhesive properties can be further evaluated to find the prospects of other mechanical properties. Therefore, the need for a standard microstructural evaluation method of the adhesive properties has also been addressed in this study.